Personal tutoring - Elaine M. Smith (2008)
This booklet takes a pragmatic approach and is aimed at those organising personal tutor systems and engineering academics who want more information about how to effectively fulfil a pastoral care role. A number of issues related to personal tutoring are presented. Alternative models of personal tutoring, the type of support needed and the student expectations of that support are considered along with identification of students at risk. Staff development and training are also highlighted. The booklet ends with a suggestion for evaluation and guidelines for implementing successful personal tutor systems. Being an academic advisor or personal tutor can be a challenging experience within any academic career. It can often be an opportunity to make a real difference to the lives of individual students but occasionally it can also be difficult and time-consuming. Whilst the vast majority of students go through their university experience without any major problems, some individuals succeed or fail as a result of their relationship with academic staff who fulfil this vital support role.